Assessment of Physical Environment of Iran's Neonatal Tertiary Care Centers from the Perspective of the Neonatal Individualized Developmental Care - Mostajab Razavi Nejad; Mohammad Heidarzadeh; Parisa Mohagheghi; Forouzan Akrami; Amir Almasi-Hashiani; Zahra Eskandary (Mashhad University of Medical Sciences, 2017)
Background: Globally,it is estimated that approximately 13 million neonates are born prematurely each year. The development of the central nervous system in premature neonates continues outside of the uterus and in the environment of neonatal intensive care unit (NICU). This study aimed to evaluate the physical environment of hospital and nursery in Iran's tertiary care centers. Methods: This cross-sectional study was conducted on a total of 23 NICUs of nine Universities of Medical Sciences, where students are trained in the neonatal fellowship course, from seven provinces of Iran, 20th July to 21th September 2015. Data analysis was performed using SPSS software, version 16, and descriptive statistics. Results: In this study, four dimensions of physical environment of hospitals and NICUs including the accessibility of NICU, the physical environment of NICU, infants' bed space, and the sensory elements of bed spaces were evaluated. The obtained scores for each item was 41.17, 39.95, 38.83, and 39.28 out of 100, respectively. The highest mean score was 71.30 that was related to NICU temperature and ventilation considerations. The lowest mean score was 20, which was related to controlling over the movements around the infants' beds. The total mean score of the physical environment of hospital and NICU was 39.77. Conclusion: According to the results, it is recommended to take appropriate action to develop physical space and infrastructures for neonatal care regarding developmental care along with other dimensions.